2009
DOI: 10.1089/hum.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Receptor Gene Therapy for Cancer

Abstract: T cell-based adoptive immunotherapy has been shown to be a promising treatment for various types of cancer. However, adoptive T cell therapy currently requires the custom isolation and characterization of tumor-specific T cells from each patient-a process that can be not only difficult and time-consuming but also often fails to yield high-avidity T cells, which together have limited the broad application of this approach as a clinical treatment. Employing T cell receptor (TCR) gene therapy as a component of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 77 publications
1
66
0
Order By: Relevance
“…4,5 , 35 Recent studies of adoptive transfer with autologous T cells generated from patients have focused on generation of genetically modified memory CD8 C T cells with chimeric antigen receptors or T-cell receptors with a particular focus on improving the proliferation and persistence of T cells after transfer. [36][37][38][39][40] Traditionally, IL-2 has been a central component of T-cell expansion protocols. [41][42][43] However, IL-2-expanded T cells have significant limitations in adoptive therapy, including susceptibility to T-cell activation-induced cell death (AICD), Treg proliferation, and T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 , 35 Recent studies of adoptive transfer with autologous T cells generated from patients have focused on generation of genetically modified memory CD8 C T cells with chimeric antigen receptors or T-cell receptors with a particular focus on improving the proliferation and persistence of T cells after transfer. [36][37][38][39][40] Traditionally, IL-2 has been a central component of T-cell expansion protocols. [41][42][43] However, IL-2-expanded T cells have significant limitations in adoptive therapy, including susceptibility to T-cell activation-induced cell death (AICD), Treg proliferation, and T-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent the lack of high-avidity tumor reactive T cells, high-affinity tumorspecific receptors can be introduced by genetic modification into T cells that comprise the native repertoire and were not subject to central tolerance. Redirection of T cell specificity to a tumor can be accomplished by introduction of transgenes encoding a and b chains that encode a TCR specific for a tumor antigen or by introduction of tumor antigen-specific chimeric antigen receptors (CARs) [10,11]. These strategies endow modified T cells with the capacity to be activated through the introduced antigen receptor or their endogenously expressed TCR; hence their designation in some studies as bi-specific T cells.…”
Section: Redirecting T Cell Specificity By Genetic Modificationmentioning
confidence: 99%
“…1 E ver since descriptions of the various functional components of the hematopoietic stem cell niche, leukemia researchers have wondered whether leukemia stem cells (LSCs) require similar cell-extrinsic support for longterm maintenance of leukemia. 2 LSCs differ from normal hematopoietic stem cells (HSCs) in that they have activation of key pathways regulating self-renewal, proliferation, and survival.…”
Section: Bad To the Bone --------------------------------------------mentioning
confidence: 99%
“…1 Using a retroviral bone marrow transplantation model of blast-crisis chronic myeloid leukemia, the authors observed that mice with leukemia had a reduction in bone trabeculae and thinning of cortical bone compared with wild-type, nonleukemic controls. These bony changes were mediated through both reduced bone formation and increased osteoclastic bone resorption, and were partially reversible by treatment with bisphosphonate therapy (to inhibit osteoclast function).…”
Section: Bad To the Bone --------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation